Analisis Keunggulan Kompetitif Dalam Memaksimalkan Media Promosi Pada Warung Rondo Mangir Banyuwangi - Ayu Wanda Febrian (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2023)
Rondo Mangir Food Stalls is a culinary tourism market located on Jl. Pringgondani, Mangir Village, Kec. Rogojampi, Banyuwangi. This culinary tourism market has a strategic place and resources with competitive advantages so that it creates considerable opportunities if developed and promoted. This study aims to introduce Rondo Mangir Food Stalls more widely through Instagram social media effectively with a resource-based approach. This study used a qualitative descriptive method with Resources Based View Theory analysis (RBV) to describe the conditions and resources owned and the VRIO analysis framework for resource assessment. The decision-making stage uses SCA analysis toward the resources that meet all the approximations used as an alternative recommendation for the promotion strategy of Rondo Mangir Food Stalls. There are three recomendations in which the elements of the promotion mix has included in each reference. The strategy resulted from the SCA analysis are making selected resources in tho form of art as content, develop management capabilities and empower communities through training or socialization to keep the operational maintenance of Rondo Mangir Food Stalls.